The Influence of Project Based Learning Model to Increase Students' Creativity in Writing Scientific Papers of Poetry - Yunita Ashari; Sekar Purbarini Kawuryan; Deri Angraini (Jurnal Penelitian Pendidikan IPA, 2025)
Higher education today increasingly emphasizes the development of students' creativity and critical thinking skills. The Project Based Learning (PBL) model has become an effective approach in this context. This study aims to evaluate the effectiveness of PBL to improve students' creativity in writing scientific literary poetry using archaic words. This research used an experimental method by dividing students into two groups: an experimental group using PBL and a control group using conventional methods. Data were then collected from pre-test and post-test scores of students in both groups, then analyzed using descriptive analysis and Wilcoxon and Mann-Whitney statistical tests. The results showed a significant increase in the ability to write poetry in the experimental group compared to the control group. The average post-test score of the experimental group increased from 30.35 to 32.43, while the control group experienced a decrease from 28.07 to 27.52. Statistical tests showed a significant difference between the two groups, with a Mann-Whitney U value of 214,000 and a significance of 0.000. These findings indicate that the implementation of PBL is effective to increase students' creativity and poetry writing skills. Therefore, the use of PBL as a learning strategy is highly recommended to develop students' creativity and learning outcomes in the context of higher education